A mixed subgrid-scale model based on ICSM and TADM for LES of surfactant-induced drag-reduction in turbulent channel flow. (25th March 2017) - Li, Jingfa; Yu, Bo; Wang, Lu; Li, Fengchen; Hou, Lei
Highlights: An improved coherent-structures Smagorinsky model (ICSM) is proposed. A mixed subgrid-scale model (MICT) combining ICSM with TADM is established. LES of turbulent drag-reducing channel flow based on MICT is carried out. The calculation performance of ICSM and MICT are better than CSM and MCT. Abstract: The coherent-structures Smagorinsky model (CSM) is an eddy viscosity subgrid-scale (SGS) model which has been successfully used in large eddy simulation (LES) of turbulent flows. However, the LES results are not in good agreement with those obtained by direct numerical simulation (DNS) in turbulent channel flow. To improve underlying demerits of CSM, the present paper proposes an improved CSM (ICSM) in which the energy-decay suppression function is defined from the perspective of physical meaning. Furthermore, a mixed SGS model which combines ICSM with TADM named MICT is established for the LES of surfactant-induced drag reduction in turbulent channel flow in this study. The main idea of MICT is to apply ICSM to perform spatial filtering for the continuity and momentum equations and adopt TADM to perform temporal filtering for the constitutive equation, respectively. Simulation results indicate that, compared with the conventional SGS models (CSM and MCT), results obtained by ICSM and MICT agree better with those of DNS.